1991
DOI: 10.1093/jn/121.9.1331
|View full text |Cite
|
Sign up to set email alerts
|

Dietary (n-3) Fatty Acids Affect Rat Heart, Liver and Aorta Protective Enzyme Activities and Lipid Peroxidation

Abstract: In a 16-wk study, weanling Wistar rats (32 males and 32 females) were fed a modified AIN-76 diet containing 20% fat with various (n-3) fatty acids. All dietary fats provided the same amount of saturates, monounsaturates, and total essential fatty acids [(n-6) + (n-3)]. The control diet contained lard/corn oil (L/CO). The other diets contained (n-3) fatty acids from linseed oil (LSO), from linseed oil + menhaden oil (LSO + MO) or from menhaden oil (MO). The (n-3) diets reduced total and HDL-cholesterol, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(46 citation statements)
references
References 26 publications
3
40
3
Order By: Relevance
“…The assumption that high doses of ALA/LA enhance oxidative stress is supported by several authors [33, 34, 35]. Furthermore, the hypothesis that carcinogenesis is increased by elevated lipid peroxidation is supported by Bartsch et al [28]who reported that free radical damage and DNA alkylation are involved in carcinogenesis induced by nitrosamines.…”
Section: Discussionmentioning
confidence: 92%
“…The assumption that high doses of ALA/LA enhance oxidative stress is supported by several authors [33, 34, 35]. Furthermore, the hypothesis that carcinogenesis is increased by elevated lipid peroxidation is supported by Bartsch et al [28]who reported that free radical damage and DNA alkylation are involved in carcinogenesis induced by nitrosamines.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, the same pathomechanism is discussed for nitrosamine-induced carcinogenesis in pancreatic cancer. Since octreotide decreased liver metastases, the influence of octreotide on oxidative stress should be analyzed in further trials [26, 27, 28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…At least four general potential mechanisms could contribute to the obesity-related myocardial lipid peroxidation: (a) increased myocardial work and subsequent radical production via mitochondrial respiration; 4 (b) decreased myocardial antioxidant defense; 12 ± 14 (c) increased fat deposition within myocardial tissue; 15,16 andaor (d) increased rates of radical formation such as superoxide (O 2 À ) or the hydroxyl radical. 17 Theoretically, it is possible that all of these mechanisms are present and participate in the increase in myocardial lipid peroxidation in obesity.…”
Section: Introductionmentioning
confidence: 99%